APPLICATION OF PERCUTANEOUS ENDOSCOPICALLY ASSISTED GASTROSTOMY IN MULTIFUNCTION HOSPITAL - A. N. Petrovsky; I. V. Vagin; S. L. Gobaeva; A. Yu. Popov; A. G. Barishev (Инновационная медицина Кубани)
Background. Optimization of the process and improved efficiency of the prolonged compulsory enteroalimentation in the patients who require it for more than 4 weeks.Materials and Methods. We analyzed the first experience of percutaneous endoscopically assisted gastrostomy in 32 patients. Patients were treated in the neurosurgical and neurologic department of Research Scientific Institute – Ochapovsky Regional Clinical Hospital no. 1 in Krasnodar.Results. Application efficiency of percutaneous endoscopically assisted gastrostomy for prolonged enteral feeding in patients with combined trauma and neurological deficiency was shown. The greatest number of complications 3 (33.3%) was observed in the group of patients with cranio-cereberal traumas.